2016
DOI: 10.1186/s11671-016-1650-z
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of Au/PAMAM contrast agent on CT imaging of reticuloendothelial system and tumor tissue

Abstract: Polyamidoamine (PAMAM)-entrapped Au nanoparticles were synthesized with distinct sizes to figure out the size effect of Au-based contrast agent on CT imaging of passively targeted tissues. Au/PAMAM nanoparticles were first synthesized with narrow distribution of particles size of 22.2 ± 3.1, 54.2 ± 3.7, and 104.9 ± 4.7 nm in diameters. Size effect leads no significant difference on X-ray attenuation when Au/PAMAM was ≤0.05 mol/L. For CT imaging of a tumor model, small Au/PAMAM were more easily internalized via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The hydrodynamic size of GQDs-LPs was measured by DLS and showed a peak centered at around 100 nm (Figure S3). Such sizes are desirable because the diameter about 100 nm is preferred to avoid a rapid renal clearance and uptake by the reticuloendothelial system. , The EE of GQDs at pH 4.0 and 10.0 was 18.31 ± 1.71% and 25.19 ± 2.12% (Figure c), respectively, which showed a significant decrease compared with that at pH 7.0 (45.68 ± 1.44%). It can be explained by the fact that the specific molecular structure of phospholipids used in this study is sensitive to the pH value.…”
Section: Resultsmentioning
confidence: 95%
“…The hydrodynamic size of GQDs-LPs was measured by DLS and showed a peak centered at around 100 nm (Figure S3). Such sizes are desirable because the diameter about 100 nm is preferred to avoid a rapid renal clearance and uptake by the reticuloendothelial system. , The EE of GQDs at pH 4.0 and 10.0 was 18.31 ± 1.71% and 25.19 ± 2.12% (Figure c), respectively, which showed a significant decrease compared with that at pH 7.0 (45.68 ± 1.44%). It can be explained by the fact that the specific molecular structure of phospholipids used in this study is sensitive to the pH value.…”
Section: Resultsmentioning
confidence: 95%
“…Theoretically, a nano-scale contrast agent may improve in vivo tumor imaging made by ultrasound, CT and magnetic resonance imaging ( 42 44 ). Kim et al ( 42 ) demonstrated that ultrasound enhanced-contrast agents, which may go preferentially to the target tumor tissue and amplify the ultrasound imaging signal in vivo , improved the detection limit of ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray imaging based on the use of radiopaque agents accumulated selectively in macrophages was recently offered as an alternative method for the detection of cellular inflammation in soft tissues. 29 33 The ability of ( 1 ), ( 2 ) and ( 3 ) to easily accumulate in macrophages makes these moieties potentially good agents for the visualisation of cellular inflammation.…”
Section: Discussionmentioning
confidence: 99%